Presentation of a benign fibroepithelial polyp with frank haematuria: an unusual diagnosis. Issue 1 (February 2015) - Dolan, R; Morton, S; Granitsiotis, P
Introduction: Fibroepithelial polyps are rare benign lesions which can mimic malignant disease symptomatically and radiologically. They should form part of the differential diagnosis in patients presenting with frank haematuria but they can present a diagnostic dilemma for clinicians. Case presentation: This is a case of a 30-year-old female who initially presented with a small palpable urethral lump, thought to be a urethral caruncle by her general practitioner, obstructive voiding and intermittent frank painless haematuria. A rigid cystoscopy identified a polypoid lesion protruding out of the left ureteric orifice. This was resected and pathology showed it to be a fibroepithelial polyp. A post-operative computerized tomography scan showed no hydronephrosis on either side and no lymphadenopathy was identified but the distal left ureter could not be visualised. Further resection with a flexible ureteroscopy confirmed the presence of a benign fibroepithelial polyp and the stalk remnant was ablated with a laser. Conclusion: Fibroepithelial polyps mimic malignant disease symptomatically and radiologically and need to be considered in the differential diagnosis of frank haematuria.